2022
DOI: 10.1002/acm2.13801
|View full text |Cite
|
Sign up to set email alerts
|

Clinical commissioning of an adaptive radiotherapy platform: Results and recommendations

Abstract: Online adaptive radiotherapy platforms present a unique challenge for commissioning as guidance is lacking and specialized adaptive equipment, such as deformable phantoms, are rare. We designed a novel adaptive commissioning process consisting of end‐to‐end tests using standard clinical resources. These tests were designed to simulate anatomical changes regularly observed at patient treatments. The test results will inform users of the magnitude of uncertainty from on‐treatment changes during the adaptive work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(53 reference statements)
2
11
0
Order By: Relevance
“…In this time period, abdominopelvic air cavities may migrate, expand, or disappear, rendering the time‐consuming manual corrections invalid. Our results are in concordance with previous studies that investigated the dosimetric effects of electron density correction for MR‐based oART 29 and gas overrides in a phantom‐base commissioning of the Ethos workflow 30 . Both studies agreed that manual correction of air volume is time consuming and has minimal clinical effect in the dose distribution.…”
Section: Discussionsupporting
confidence: 92%
“…In this time period, abdominopelvic air cavities may migrate, expand, or disappear, rendering the time‐consuming manual corrections invalid. Our results are in concordance with previous studies that investigated the dosimetric effects of electron density correction for MR‐based oART 29 and gas overrides in a phantom‐base commissioning of the Ethos workflow 30 . Both studies agreed that manual correction of air volume is time consuming and has minimal clinical effect in the dose distribution.…”
Section: Discussionsupporting
confidence: 92%
“…Before each treatment session, the presence of gas on CBCT is vigilantly monitored or removed, if deemed necessary. This approach is consistent with the investigation conducted by Kisling et al 10
Figure 3 Comparison of CBCT and synthetic CT images with (A) biliary stent, (B) air bubbles, and (C) bolus. (A) The purple-colored high-density structure from the synthetic CT overlaps with the biliary stent on the CBCT, enabling acceptable dose calculation.
…”
Section: Methodssupporting
confidence: 88%
“…Despite a few published articles on commissioning and dosimetric studies of the CBCT-based OART platform, 9 , 10 , 11 , 12 , 13 a pressing need remains for published guidance on the comprehensive treatment workflow and individual responsibilities. In this study, we conducted a failure mode and effects analysis (FMEA) to identify high-risk failure modes and developed logistically feasible clinical workflows for OART, which are categorized into 4 components: 1 site-specific templates preparation, 2 pretreatment planning and verification, 3 on-treatment procedures, and 4 posttreatment verification, along with safety checklists.…”
Section: Introductionmentioning
confidence: 99%
“…Kisling et al observed an average of 1.6% difference between phantom ion chamber measurements and synthetic CT doses, even when simulating weight losses and gains of up to 4 cm, which are more extreme than the differences expected in this study. 26 Additionally, Nelissen et al observed <2% dose disparity between the synthetic CT and CBCT in high dose regions for palliative spine treatment. 27 Although smaller calculation grids are preferred for SBRT plans, the Ethos platform (v1.1 MR3) offers a minimum optimization and dose calculation resolution of 2.5 mm at this time.…”
Section: Discussionmentioning
confidence: 99%